Diversity and Distribution of Cyatholaimidae (Chromadorida: Nematoda): A Taxonomic and Systematic Review of the World Records - Cunha, Beatriz P.; Fonseca, Gustavo; Amaral, A. Cecilia Z. (Frontiers in Marine Science, 2022)
Nematoda is a very species-rich phylum that has successfully adapted to almost all types of ecosystems. Despite their abundance and ecological importance, the taxonomic knowledge of nematodes is still limited and the identification of species is not trivial. In Cyatholaimidae, a relatively common and abundant family of free-living nematodes, the identification of organisms is challenging due to the overlap of some generic diagnoses and the absence of updated systematic reviews. Here we systematically reviewed the knowledge about the family diversity, providing a list of valid species, the diagnostic characters to genus level, and the geographical and habitat distribution of species. The review systematized a total of 619 records. The occurrences were classified into biogeographic ecoregions and habitats. Cyatholaimidae includes 211 valid species, classified in 20 genera. The genera can be differentiated based on six diagnostics characters, namely: pattern of cuticle ornamentation; number of longitudinal rows of pore-complex in cuticle; structures of the buccal cavity; presence/absence of pharyngeal bulb; pre-cloacal supplements aspect; and the shape of gubernaculum. Cyatholaimidae includes mainly marine species, mostly occurring in the Coastal Zone. Four and three species were registered in freshwater and terrestrial habitats, respectively, all classified in the genus Paracyatholaimus. About 38% of the valid species occur in more than one type of habitat, under very different environmental conditions, suggesting a broad niche. The occurrence of congeneric species in different habitats types indicates that, throughout the evolutionary history of the family, multiple ecological shift events have occurred. The family occurs worldwide in 74 ecoregions, and the majority of the records and species are in the North Sea and Western Mediterranean. Most species are endemic to one ecoregion, and examples of broadly distributed ones may be a result of misidentifications or cases of long-distance dispersal, especially for those associated with biological substrates.